Effect of test concentration in the ready biodegradability test for chemical substances: Improvement of OECD test guideline 301C. (3rd December 2015) - Nabeoka, Ryosuke; Taruki, Masanori; Kayashima, Takakazu; Yoshida, Tomohiko; Kameya, Takashi
Abstract: In Japan, understanding the environmental persistence of chemicals is very important for risk assessment, and ready biodegradability tests are mainly conducted according to the Organisation for Economic Co‐operation and Development test guideline 301C. However, the highest test concentration specified in test guideline 301C, 100 mg/L, may cause microbial toxicity and incomplete biodegradation. The authors performed test guideline 301C tests at test concentrations of 30 mg/L for 13 substances that were readily biodegradable in ready biodegradability tests but not in test guideline 301C tests. Of the 5 substances with potential to cause microbial toxicity at 100 mg/L, the percentage of biodegradation of sodium dimethyldithiocarbamate, 4‐chloro‐3‐cresol (CC), thymol (THY), and p ‐ tert ‐butyl‐ α ‐methylbenzenepropionaldehyde measured by biochemical oxygen demand (BOD) increased in the test guideline 301C test at 30 mg/L, suggesting a reduction in toxicity effects. Furthermore, CC and THY met the criteria for ready biodegradability, which are more than 60% of biodegradation by BOD and a 10‐d window. Of the 8 substances with a low potential for causing microbial toxicity at 100 mg/L, the percentage of biodegradation of only 2‐(diethylamino)ethanol increased in the test guideline 301C test at 30 mg/L. Employing a lower test concentration in the standard test guideline 301C test will contribute to improvement of consistency between results of a test guideline 301C test and other ready biodegradability tests. Environ Toxicol Chem 2016;35:84–90. © 2015 SETAC